2010
DOI: 10.1063/1.3319839
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage nanodomain writing in He-implanted lithium niobate crystals

Abstract: A scanning force microscope tip is used to write ferroelectric domains in He-implanted singlecrystal lithium niobate and subsequently probe them by piezoresponse force microscopy. Investigation of cross-sections of the samples showed that the buried implanted layer, ∼ 1 µm below the surface, is non-ferroelectric and can thus act as a barrier to domain growth. This barrier enabled stable surface domains of < 1 µm size to be written in 500 µm-thick crystal substrates with voltage pulses of only 10 V applied to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The presence of a thin layer of ferroelectric crystal greatly simplifies the process of creating waveguide structures by Ti implantation or proton exchange methods. Moreover, the thin crystal layers of LiNbO 3 and LiTaO 3 ferroelectric crystals allow for the formation of nanoscale domain structures [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a thin layer of ferroelectric crystal greatly simplifies the process of creating waveguide structures by Ti implantation or proton exchange methods. Moreover, the thin crystal layers of LiNbO 3 and LiTaO 3 ferroelectric crystals allow for the formation of nanoscale domain structures [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fluences needed for good optical confinement using light ion implantation are very high, of the order of 10 16 -10 17 at/cm 2 . Interestingly, the use of buried damaged layers produced by ion implantation have been found to be good for producing easier, better and smaller domain reversal patterning in LN with nanometer sizes [16][17][18] Recently, the use of irradiations with heavier ions (i.e. A > 10) at higher energies (≥ 1 MeV/amu, also called swift heavy ions or SHI) such that the maximum electronic energy loss (or stopping power, Se) takes place some microns underneath the surface, has been proposed for fabricating good and novel optical waveguides in LiNbO 3 [19][20][21] and other oxides [22,23] with the pragmatic benefit of using fluences several orders of magnitude lower than those used with light ion implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that sub-micrometer-sized surface domains can be written in He-irradiated LiNbO 3 crystals by applying voltage pulses to the tip of a scanning probe microscope [22]. In this paper, we present a detailed analysis of this technique and in particular the dependence of the domain formation on both the pulse (voltage and duration) and the irradiation parameters (energy and fluence), hence providing a deeper understanding of the poling process.…”
Section: Introductionmentioning
confidence: 99%